Plasmodium species infecting lizards in the Brazilian Cerrado: Identification and description of a novel species, Plasmodium brasiliensis n. sp. - Izabelle T S Carvalho; Adriana P Furtado; Matheus A Duarte; Pedro H O Pereira; Lívia S M Paiva; Júlio M A Silva; Guarino G Colli; Erika M Braga; Giane R Paludo (PLoS ONE)
Parasites of the genus Plasmodium, responsible for lizard malaria, are widely distributed and taxonomically diverse. Molecular techniques provide valuable insights into the evolutionary relationships of Plasmodium species and lineages. However, the available data are still scarce, emphasizing the need for taxonomy-focused studies. We investigated the occurrence of Plasmodium infection in free-living lizards in the Brazilian Cerrado using an integrative approach based on the amplification/sequencing of the Plasmodium cytb gene and microscopic analysis. Among 302 lizards screened, 61 (20.2%) tested positive in the molecular screening, including 18 with concordant results in microscopy. We recovered 16 sequences in the first molecular survey of this host group in the biome. Our findings unveil a variety of Plasmodium species, some of which were previously undocumented in this region. We describe new lineages of Plasmodium ouropretensis, P. tropiduri, P. carmelinoi, and also report a new species, herein named as Plasmodium brasiliensis n. sp. The infection by Plasmodium sp. in Hoplocercus spinosus represents the first description of Apicomplexa organisms in this species. Furthermore, our results open remarkable possibilities for extensive studies in a field unexplored for many years.